(untitled) (Journal of the College of Education for Women, 2024)
The problem of study is the challenges faced by EFL students in learning and mastering collocations. This study aims to determine the effect of using Dictogloss Technique on students’ collocation knowledge. In order to achieve the aim of this research and verify its hypotheses, a sample of 60 Students has been randomly chosen from the second course of study in the University of Baghdad College of Education for Women during the academic year: 2023 – 2024. The two groups are randomly assigned to group (A), which is the control group consisting of 30 students who were taught using a Dictogloss Technique, and group (B), which is the experimental group, consisting of 30 students taught using a traditional manner. This study is measured by administering pretests and posttests, Certain variables have been equalized for both groups. A statistical analysis has been performed on the information obtained from the post-test results. These results reveal that the experimental group was superior to the control group in the posttests for collocation knowledge. The outcomes show how the Dictogloss Technique enhances students’ knowledge and understanding of collocations. Data is collected and analyzed by using SPSS v26.